Community Participation-Based Environmental and Health Management in Dhaka City Suburban Slum Areas - Yaesin, Tupo; Jobin, Mhotin; Mahedi, Hussain (Journal of Asian Multicultural Research for Economy and Management Study, 2022)
The purpose of this article is to identify the role of the community in dealing with the problem of slum housing in the city of Dhaka with several approaches, namely collaboration between organizations and the role of the community itself. Several programs that have been implemented to solve this problem are public housing, slum reconstruction program, and Approach to Basteess. The potential of the impoverished to improve their living conditions and hence their productivity and income is demonstrated by the housing projects implemented by non-governmental organizations. Living under these conditions can lead to a variety of negative consequences, including decreased health, increased pollution, the spread of illness, and even criminal conduct. It is considered a disease in the city to have slums. It is considered a disease in the city to have slums. Build a residential environment that is conducive to various aspects of human progress in order to quickly achieve poverty reduction via comprehensive human development.